Effectiveness of Local Point Acupuncture and Auricular Acupuncture Therapy on Basic Functional Ability of Knee in Knee Pain Patients in Kedungwringin Village, Banyumas Regency - 'Aini, Fatimah Qurrota; Sumanto, Sumanto; Badri, Sholichan (Indonesian Journal of Acupuncture, 2024)
Knee pain is a disorder of the knee joints felt by most people in the world where a person feels pain and movement limitations while doing activities. Several factors cause knee pain, one is degenerative factors. Acupuncture therapy can provide a relaxing effect, improve circulation, repair damaged tissue, and reduce pain in the knee. This study aimed to determine the effectiveness of local point acupuncture therapy and auricular acupuncture on the basic functional abilities of the knee in patients with knee pain in Kedungwringin Village, Banyumas Regency. This study used quantitative research with a “Quasi-Experimental” research design. The sample of the research study was 45 people divided into three treatment groups, namely group I auricular acupuncture therapy, group II local point acupuncture therapy, and group III auricular acupuncture therapy and local point acupuncture. This study started from February to April 2024 and was conducted in Kedungwringin Village, Banyumas Regency. The One Way Anova test analysis of each group has a significant value ρ<0.05 (ρ=0,007) which means Ha is accepted and H0 is rejected so that it can be interpreted that local point acupuncture therapy and auricular acupuncture are effective on the basic functional abilities of the knee in patients with knee pain.